IMPLEMENTASI CORPORATE SOCIAL RESPONSIBILITY PADA PT. ANEKA TAMBANG Tbk. UBPN SULAWESI TENGGARA - Candra Puspita Ningtyas; Makmur Kambolong; Munawir Makmur (Halu Oleo University, 2022)
Corporate Social Responsibility (CSR) is very important for companies, especially by companies whose operational activities have an impact on the community and the surrounding environment. Especially mining companies are important to carry out CSR programs. CSR implementation is carried out as a form of corporate social responsibility. This research provides an overview of the implementation of Corporate Social Responsibility (CSR) implemented by PT.Antam, Tbk. Explained in the study of literature from the economic , social, and environmental aspects. The realization of CSR in the economic aspect is realized by PT. Antam, Tbk by contributing to the community and the Government which aims to increase the economic independence of sustainability and prosperity and contribute to the Government through the payment of non-tax state revenues (PNBP), taxes, and royalties amounting to Rp758.81 billion. Efforts to combat poverty in the Company's operational areas are realized in the Partnership Program in the form of capital assistance to foster partners. Enviromental aspects by ANTAM implements Good Mining Practice covering aspects healthy and work safety, environment responsibility, community development, post mining plan. CSR Antam is important because in addition to building a positive image by company for the welfare of the community so that there is a harmonious relationship between the company and the community as part of the stakeholder.